2010
DOI: 10.1007/s10439-010-0195-z
|View full text |Cite
|
Sign up to set email alerts
|

Contractility Dominates Adhesive Ligand Density in Regulating Cellular De-adhesion and Retraction Kinetics

Abstract: Cells that are enzymatically detached from a solid substrate rapidly round up as the tensile prestress in the cytoskeleton is suddenly unopposed by cell–ECM adhesions. We recently showed that this retraction follows sigmoidal kinetics with time constants that correlate closely with cortical stiffness values. This raises the promising prospect that these de-adhesion measurements may be used for high-throughput screening of cell mechanical properties; however, an important limitation to doing so is the possibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
5
9
0
Order By: Relevance
“…Specifically, for a given pre-stretch, with increase in substrate stiffness, pre-stress initially increases and then saturates on stiffer substrates. Furthermore, on a substrate of given stiffness, as contractility increases, cell de-adhere faster, as is experimentally observed in faster de-adhesion of cells treated with contractility-activating drugs like LPA and nocodazole [9], [10]. Collectively, these results demonstrate how substrate stiffness influences de-adhesion dynamics via modulation of cell contractility.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Specifically, for a given pre-stretch, with increase in substrate stiffness, pre-stress initially increases and then saturates on stiffer substrates. Furthermore, on a substrate of given stiffness, as contractility increases, cell de-adhere faster, as is experimentally observed in faster de-adhesion of cells treated with contractility-activating drugs like LPA and nocodazole [9], [10]. Collectively, these results demonstrate how substrate stiffness influences de-adhesion dynamics via modulation of cell contractility.…”
Section: Discussionsupporting
confidence: 71%
“…Consequently, de-adhesion timescales depend both on the initial state of the cystokeleton and the rate of bond breakage. This has been demonstrated in previous experiments where contractile stimulation via drugs including LPA and nocodazole, or faster dis-assembly of adhesions effected by using a higher concentration of trypsin, both led to faster de-adhesion [9], [10]. Such a coupled dependency of on the two factors can be appreciated from the analytical expression  = .…”
Section: Discussionmentioning
confidence: 53%
“…It has also been shown that continuous culture models of GBM require myosin II and its upstream regulators to sense and respond to ECM rigidity (4,5,37,38). However, it has remained unclear if these principles apply to primary TICs, or if manipulation of the mechanosensing machinery can influence tumor initiation and progression in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…or density (15)(16)(17). More specifically, one can modulate the stiffness of these materials as an isolated variable by manipulating cross-linking density in ways that do not require addition of more matrix ligand (i.e., fibrinogen), which could independently alter platelet function and confound interpretation of results.…”
Section: Differential Platelet Adhesion and Spreading On Immobilizedmentioning
confidence: 99%